Hybrid Vigour Study of Yield and Yield Related Characters on Limmu Coffee (Coffea arabica L.) Genotypes at South-Western Ethiopia - Asefa, Gemechu; Mohammed, Hussein; Ayano, Ashenafi (Journal of Tropical Crop Science, 2021)
Coffee (Coffea arabica L.) is one of the most important crops cultivated worldwide and has a great economic impact in many countries including Ethiopia. Hybrid vigor (heterosis) breeding can enhance productivity of coffee. Hybrid vigor study was conducted on 5 x 5 half-diallel mating involving 17coffee genotypes (5 parents, 10 F1 hybrids and two checks) for yield and its related traits in 2018. The study locations include Jimma, Agaro and Gera research centers of south-western Ethiopia using randomized completely block design with three replications. There are significant differences among 17 genotypes and 15 diallel genotypes (checks excluded) for all traits; the crosses showed significant and positive average heterosis (mid parent) and heterobeltiosis (better parent) for all traits. Crosses showed significant variation in the expression of standard heterosis (SH) and useful heterosis (UH) for fruit length (FL), fruit width (FW), bean length (BL), bean width (BW), bean thickness(BT), and hundred bean weight (HBW) across locations. Heterobeltiosis ranged from -9.06 to 88.79% and -17.81 to 67.98% for yield at Jimma and Gera, respectively. Mean SH and UH was positive and between 5 and 10% for BL and BT and <5% for all fruit characters and BT across locations. Mean of SH and UH was 14.62% and 11.82%, respectively for HBW. Crosses P4 x P5, P1 x P5 and P2 x P5 increased yield by 25.13% (637.75 kg), 14.05% (356.64 kg) and 5.78% (146.59 kg) over commercial pure line variety across three locations, respectively. Based on heterosis and mean performance hybrids P4 x P5, P1 x P5, P3 x P5, and P1 x P2 found as promising hybrids for yield and bean characters. Thus, these hybrids should be advanced in the next breeding program and tested through incorporating other traits.